2011 IEEE International Geoscience and Remote Sensing Symposium 2011
DOI: 10.1109/igarss.2011.6049401
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear unmixing of hyperspectral images using radial basis functions and orthogonal least squares

Abstract: This paper studies a linear radial basis function network (RBFN) for unmixing hyperspectral images. The proposed RBFN assumes that the observed pixel reflectances are nonlinear mixtures of known endmembers (extracted from a spectral library or estimated with an endmember extraction algorithm), with unknown proportions (usually referred to as abundances). We propose to estimate the model abundances using a linear combination of radial basis functions whose weights are estimated using training samples. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…1) Conditional pdf : Straightforward computations lead to (13) where . Since it is not easy to sample according to (13) [mainly because of the indicator function ], we propose to update the abundance using a Metropolis-Hasting move.…”
Section: E Metropolis-within-gibbs Samplermentioning
confidence: 99%
See 2 more Smart Citations
“…1) Conditional pdf : Straightforward computations lead to (13) where . Since it is not easy to sample according to (13) [mainly because of the indicator function ], we propose to update the abundance using a Metropolis-Hasting move.…”
Section: E Metropolis-within-gibbs Samplermentioning
confidence: 99%
“…Since it is not easy to sample according to (13) [mainly because of the indicator function ], we propose to update the abundance using a Metropolis-Hasting move. More precisely, a new abundance coefficient is proposed following a Gaussian random walk procedure (the variance of the proposal distribution has been adjusted to obtain an acceptance rate close to 0.5, as recommended in [26, p. 8]).…”
Section: E Metropolis-within-gibbs Samplermentioning
confidence: 99%
See 1 more Smart Citation
“…Bilinear models recently studied in [3,4] have shown interesting properties for images subjected to scattering effects, i.e., observed in wooded areas. Other more flexible unmixing techniques have also been proposed to handle wider class of nonlinearities, including radial basis function networks [5,6] and kernel-based models [7]. This paper considers a kernel-based approach for unsupervised SU based on a nonlinear dimension reduction method referred to as Gaussian process latent variable model (GP-LVM).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several hyperspectral imaging-based spectral unmixing algorithms have been gradually introduced into MODIS FSC mapping. Zhang et al (2015) produced MODIS FSC maps using a fully constrained least squares spectral mixture analysis method (FCLS) [30], fully constrained scaled gradient method (FCSGM) [31], a sparse regression method (SPARSE) [32] and a polynomial nonlinear method (POLY) [33,34] for the Tibetan Plateau. Although they found that all of these algorithms can improve the accuracy of snow-cover mapping compared with the MOD10A1 FSC, they also showed that complex terrain can greatly reduce the accuracy of these spectral unmixing algorithms [35].…”
Section: Introductionmentioning
confidence: 99%